Effects of Reaction Temperature on Microstructure and Advanced Pseudocapacitor Properties of NiO Prepared via Simple Precipitation Method - Sun, Qiangqiang; Bao, Shujuan (Nano-Micro Letters, 2013)
Morphology-controlled synthesis and large-scale self-assembly of nanoscale building blocks into complex nanoarchitectures is still a great challenge in nanoscience. In this work, various porous NiO nanostructures are obtained by a simple ammonia precipitation method and we find that the reaction temperature has a significant impact on their microstructures. Nanoflowers and nanoflakes have been obtained at 0°C and 50°C, while, weakly self-assembly nanoflowers with nanoflakes are formed at 20°C. In order to understand the process-structure-property relationship in nanomaterial synthesis and application, the as-prepared NiO is used as supercapacitor electrode materials, and evaluated by electrochemical measurement. The experimental results indicate that the material obtained at lower temperature has higher pseudocapacitance, the specific capacitance of 944, 889 and 410 F/g are reached for the materials prepared at 0°C, 20°C and 50°C and further calcined at 300°C, respectively. While the material obtained at higher temperature has excellent rate capacity. This offers us an opportunity searching for exciting new properties of NiO, and be useful for fabricating functional nanodevices.